Treatment expectations and patient-reported outcomes of nusinersen therapy in adult spinal muscular atrophy - Osmanovic, Alma (J Neurol, 2020)
BACKGROUND: The antisense-oligonucleotide (ASO) nusinersen has recently been approved as the first genetically modifying therapy for 5q-associated spinal muscular atrophy (SMA) based on randomized sham-controlled trials in infants and children. The efficacy in adults with long disease history and advanced disease status is still widely unknown; the same applies to specific expectations of adult SMA patients and to what extent they are met and may impact outcome measures. METHODS: In a longitudinal monocentric study in adult patients with SMA types 2–4, the Stanford Expectations of Treatment Scale (SETS) was assessed prior to and during nusinersen treatment. Treatment outcome was evaluated using patient-reported outcomes (PROs) as well as objectively quantifiable motor outcome measures. RESULTS: Adult SMA patients had high expectations of nusinersen treatment effectiveness regarding increase in muscle strength and disease stabilization. Via PROs, 75% stated improvements in muscle strength, endurance and independence under therapy which was in line with slight improvements in quantifiable motor scores during a  ten month observation period. In contrast, patients only expressed few negative expectations which further decreased during therapy. CONCLUSIONS: This study showed mainly positive treatment expectations and PROs in patients undergoing nusinersen treatment along with measurable functional improvement in adult SMA patients. Moreover, treatment expectations did not significantly influence outcome measures. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00415-020-09847-8) contains supplementary material, which is available to authorized users.